2000
DOI: 10.1080/095851800362454
|View full text |Cite
|
Sign up to set email alerts
|

Eye movement desensitization and reprocessing (EMDR) for post-traumatic stress disorder (PTSD) following homicide

Abstract: Homicide perpetrators have been observed to report symptoms of post-traumatic stress disorder (PTSD) directly related to involvement in the offence itself. A single case-study is presented, which describes the application of eye movement desensitization and reprocessing (EMDR; Shapiro, 1995) for a male perpetrator of homicide. The nature of the dif culties these offenders experience is considered and the need for appropriate psychological intervention in such cases is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 15 publications
1
11
0
1
Order By: Relevance
“…However, results of the present case study are consistent with EMDR for Offence-Related Trauma 15 a previous case study involving the treatment of offence-related trauma for homicide (Pollock, 2000) and lend further support for the application of EMDR for this specific type of trauma presentation. As a single case study, it is not possible to generalise findings to all offenders and this highlights the need for rigorous research targeting offence-related trauma with EMDR.…”
Section: Emdr For Offence-related Trauma 14supporting
confidence: 79%
See 3 more Smart Citations
“…However, results of the present case study are consistent with EMDR for Offence-Related Trauma 15 a previous case study involving the treatment of offence-related trauma for homicide (Pollock, 2000) and lend further support for the application of EMDR for this specific type of trauma presentation. As a single case study, it is not possible to generalise findings to all offenders and this highlights the need for rigorous research targeting offence-related trauma with EMDR.…”
Section: Emdr For Offence-related Trauma 14supporting
confidence: 79%
“…Despite the potential utility for EMDR to be applied with offenders presenting with offence-relating trauma in order to possibly reduce re-offending, only three published studies have examined EMDR with offenders (Pollock, 2000); all of which report positive EMDR effects. One was a single case study examining the effects of EMDR with a homicide offender with offence related trauma (Pollock, 2000).…”
Section: Emdr For Offence-related Traumamentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, there are only five published case studies investigating PTSD treatment effects in patients with PTSD resulting from offending (CBT: Kayrouz & Vrklevski, 2015;Lad, 2013;Rogers, Gray, Williams, & Kitchiner, 2000;EMDR: Clark, Tyler, & Gannon, 2014;Pollock, 2000). All studies showed large reductions in offense-related PTSD symptoms, as well as improved functioning.…”
Section: Introductionmentioning
confidence: 99%